Human influenza pandemics: Myth and reality - TSIODRAS, S. (Journal of the Hellenic Veterinary Medical Society, 2017)
This paper attempts to shed light in certain questions and false beliefs about seasonal, avian and pandemic influenza, mainly focusing on issues surrounding pandemic influenza. Important similarities and differences exist between seasonal, avian and pandemic influenza. Historical lessons from old pandemics help in recognizing their significant social, economical and political impact and guide the current preparedness for a future human pandemic. Currendy circulating strains, such as the avian influenza H5N1 strain constitute a danger to public health and have significant pandemic potential. Regarding clinical characteristics it appears that disease associated with a pandemic will have a high case fatality rate especially in vulnerable populations. Furthermore, the need for confirmatory diagnostic testing will likely diminish as a pandemic progresses. With regards to management stockpiling one antiviral agent will probably not be enough. No uniform scientific conclusion about the success of a prepandemic H5N1 vaccine has been reached yet. Complete pandemic plans that address subtle issues surrounding stockpiling antivirals and prepandemic vaccines as well as non-pharmaceutical measures need to be ready and to be tested in practice in order to identify problems with implementation and gaps in preparedness.